DIVERSITY OF JAMBI SOCIETY MYTHS; A CRITICAL STUDY OF THEIR MEANING AND VALUE OF USE - Fitriah, Yundi; Kusmana, Ade; Aprillitzavivayarti; Gunawan, Indra; Tersta, Fricilla Wulan (Prosiding Konferensi Internasional Kesusasteraan, 2025)
The purpose of this paper is to describe the diversity of myths in Jambi society; their meaning and usefulness. The method used is a field study to obtain data sources and the meaning of myths in society. The research technique of literature study is primarily in discussing and concluding descriptively-qualitatively to understand the benefits of myths in Jambi society. Through a qualitative approach, the data obtained are interpreted based on the time of use and the purpose of the myth conveyed. After the discussion, it was found that the diversity of myths in Jambi society is the myth of birth, circumcision, marriage, and death. Birth myths such as, during Maghrib prayer, pregnant women are not allowed to leave the house, meaning that the baby in the womb is not disturbed by spirits. The useful value of not leaving the house at Maghrib prayer is to increase discipline in performing Maghrib prayer on time. The myth during circumcision is that a circumcised child is not allowed to eat eggs, durian, goat, spicy food, and sour food. The meaning of this myth is so that the child's body does not easily become hot, and the wounds experienced will heal quickly so that it is useful to be careful in consuming food. A myth surrounding marriage is that marriage is not permitted during the months of Safar or Muharram. The myth is that marrying in Safar or Muharram is believed to bring bad luck to the bride and groom. The benefit of this myth is that it fosters a sense of independence and understanding that marriage is not prohibited in any Arabic month. A myth surrounding death is that one should not cry or mourn. This myth's meaning is to avoid disturbing the deceased's spirit, and its benefit is to foster patience, sincerity, and faith in Allah SWT in the family left behind.